The Correlation Between Resting Heart Rate and Aerobic Capacity (VO₂max) in Sports Science Students - Resti Nurpratiwi; Citra Adhitya Putri; Zefanya Putri Amelia Fo'eh; Suci Nurmarisa; Adelia Gita Pratiwi (Universitas Negeri Surabaya, 2026)
Background: research background Resting heart rate (RHR) and maximal oxygen uptake (VO₂max) are important indicators of cardiovascular health and physical fitness. Regular aerobic training is known to reduce RHR and enhance VO₂max through cardiovascular adaptations. However, the relationship between these variables in physically active sports science students has not been fully established, highlighting the need for further investigation. Objectives: This study aims to investigate the relationship between resting heart rate (RHR) and aerobic capacity (VO₂max) among sports science students. Methods: The research was conducted using a descriptive quantitative design with an observational-analytic approach. A total of 30 physically active students aged 19–22 years were selected through purposive sampling. RHR was measured using a digital blood pressure monitor and pulse palpation, while VO₂max was estimated using the 12-minute Cooper test. Statistical analysis revealed a significant negative correlation between RHR and VO₂max (r = –0.514, p = 0.004), indicating that students with lower RHR tend to have higher aerobic capacity. Results: The results reinforce the physiological understanding that cardiovascular adaptations from regular aerobic exercise—such as increased stroke volume and enhanced parasympathetic tone—contribute to reduced RHR and improved VO₂max. Conclusion: These findings suggest that RHR can serve as a practical, non-invasive indicator of cardiorespiratory fitness, particularly in populations undergoing structured physical training.